The prevalence of impairments and disabilities and their place in the community [OZURLULUK VE SAKATLIK PREVALANSI VE TOPLUMDAKI KONUMLARI] - (:unkn) unknown (My University, 1995)
The prevalence of impairments and disabilities in the Beylik Bagi district of Kocaeli were 3.58 % and 3.19 % respectively. In 31 % of the impaired, and 46 % of the disabled this condition was congenital. The most frequently seen impairment was visual impairment (42%); whereas the most frequently seen disability was locomotor disability (33 %). The percentage of consanguineous marriages was 19 % in the impaired and 37 % in the disabled (x2 = 4.975, p<0.05); 89.1 % of the impaired and 15.7-36.8 % of the disabled could carry on with the activities in daily living normally as other members of the household. One fourth of the impaired and more than half of the disabled were illiterate. Almost half of the the impaired males and merely 15.7 % of the disabled males could work and bring income.
Keywords: Community; Disability; Impairment